Spatial econometric methods in agricultural economics using R / Paolo Postiglione, Roberto Benedetti [and] Federica Piersimoni, editors. - Postiglione, Paolo; Benedetti, Roberto; Piersimoni, Federica (CRC Press, 2022)
The methods and techniques presented in this book are focused on spatial data and its use in monitoring agricultural resources, farms management, and regional markets. The authors introduce spatial econometrics models for the different data types relevant to the statistical units adopted in typical agricultural economics analyses. The theory of each model or procedure described is complemented by examples on real data that are developed by using the open-source software R. In this way, the readers can repeat these analyses on their own data. The different phases of agricultural data collection, analysis, and integration are described in a simple and intuitive way. The joint use of statistical methods, new technologies, and economic theory is treated with particular reference to the peculiarities of spatial data for a proper and efficient analysis of agricultural data sets"--